Estimation of ice strength limits for uniaxial compression in the Sea of Okhotsk according to measurements and calculations - S. V. Godetsky; O. V. Kokin; O. A. Kuznetsova; A. S. Tsvetsinsky; V. V. Arhipov (Лëд и снег)
The data on the strength of sea ice obtained in the course of explorations in the Sea of Okhotsk are compared with the results of calculations for the purpose to test the applicability of analytical methods to the conditions of this Sea. Two groups of samples were used to determine the ice strength limit. The first group included samples obtained from smooth drifting ice fields, and the second one were samples obtained from ice blocks similar to hummocks on a surface of an ice field. The measured characteristics of the temperature and electrical conductivity of ice were used in calculations using empirical formulas. The calculated values of the ice strength limits were compared with the measurements. Note, that application of the ISO 19906:2008 methodology (International Technical Standard) provided greater variety of strength values of both smooth and hummocky ice, and the SP 38.13330.2012 methodology (Russian Technical Standard) underestimated the values. The algorithms from the «Guidelines for Calculating Ice Strength Limits» are suitable for estimating mean values, but do not provide comparable root-mean-square deviation values with real data of direct measurements. The results of calculating the strength characteristics allow us to conclude that to obtain the extremely possible strength values the direct measurements (field tests) are necessary. ISO 19906:2008 is most suitable for estimating the values of smooth ice from the methods under consideration, and the algorithm from the «Methodical Letter on calculating Ice Strength Limits» is better to use for an average assessment of ice blocks.